Evaluation of Probable Sarcopenia’s Prevalence in Hospitalized Geriatric Patients Using Ishii’s Score - Cavalheiro, Ana (2023)
Background: Sarcopenia is defined as a progressive loss of skeletal muscle mass and strength related to age and comorbidities. Worldwide sarcopenia's prevalence varies between 10-40%, being associated with functional impairment, lower quality of life, and higher mortality. Sarcopenia can be estimated based on age, calf circumference, and handgrip strength (Ishii's formula). Early diagnosis is essential because treatment with nutritional support and rehabilitation programs can prevent complications. The aim of the study was to assess the prevalence of probable sarcopenia in hospitalized patients using Ishii's score and possible associated risk factors. Methods: We developed an observational prospective study in a medicine inpatient ward of a Central Hospital. We applied Ishii's formula to the patients admitted to the medical ward in December 2021 and January 2022. Patients should be aged 60 or above and able to collaborate with the tests. One year later, we analyzed re-hospitalization and mortality rates. Patients with edema of the lower limbs, who were not able to follow instructions, and who were admitted exclusively for symptomatic treatment were excluded. Results: Our final sample was 49 patients (55% males, mean age 78 ± 8.88 years). Only one patient had a previous diagnosis of sarcopenia. Estimated sarcopenia´s prevalence was 73.5% N=36), higher in men and people with three or more comorbidities. In the sarcopenic group, 77% had some degree of functional dependency and positive markers for malnutrition. After one year of follow-up, we found a higher mortality rate in the sarcopenic group (44.4% against 7.6%) and a higher number of re-hospitalizations (1.03 hospitalizations per patient, against 0.31). Conclusions: Our data showed that the prevalence of probable sarcopenia is high, but this pathology is still underdiagnosed. Traditional diagnosis is complex in some hospital settings and a simple tool such as Ishii's score can help to improve diagnostic rates. We suggest screening all patients at admission to provide early rehabilitation and nutritional support.